Clarifying Four Key Issues Regarding Letters of Credit: The Most Important International Payment Method - Xu, Yongdong (Asia Pacific Economic and Management Review, 2025)
As one of the most significant payment methods in international trade, letters of credit have greatly facilitated the settlement of international trade transactions and promoted the development of global commerce. This paper examines four key aspects of letters of credit. Firstly, their origins and evolution: from the Roman Empire to 19th-century Britain, culminating in the implementation of UCP600 on 1st July 2007, letters of credit have undergone extensive development throughout human history. Secondly, the issuance of letters of credit is subject to stringent restrictions and requirements. Upon the applicant’s submission of an application, the bank verifies their qualifications and creditworthiness. If compliant, the issuing bank issues the letter of credit upon the applicant’s deposit of a security deposit. Thirdly, the fundamental principles of letters of credit are central to our profound understanding of their core and essence. Letters of credit constitute a documentary transaction, necessitating documentary consistency and documentary compliance. Finally, examining the operational procedures of letters of credit aids in comprehending how they facilitate international trade settlements.